Green synthesized FeNPs ameliorate drought stress in Spinacia oleracea L. through improved photosynthetic capacity, redox balance, and antioxidant defense - Javeria Naseem; Anis Ali Shah; Sheeraz Usman; Shakil Ahmed; Mansour K. Gatasheh; Shifa Shaffique; Sumera Javad (Scientific Reports)
Abstract The present study was designed to highlight the ameliorative role of iron nanoparticles (FeNPs) against drought stress in spinach (Spinacia oleracea L.) plants. A pot experiment was performed in two-way completely randomize design with three replicates. For drought stress three levels were used by maintaining field capacity of the soil. This included control (100% field capacity), moderate drought stress (D1; 50% field capacity) and severe drought stress (D2; 25% field capacity). FeNPs synthesized by green method using rice straw were applied along with precursor FeCl3, used as Fe source for the synthesis of FeNPs, through foliar spray (40 mg L− 1 for both). Growth parameters, efficiency of photosynthetic machinery, gas exchange attributes, total soluble proteins, and inorganic ions (Ca2+, K+ & Fe2+) were significantly reduced at both D1 and D2 stress levels, compared to control plants. Fe supplements in the form of FeCl3 and FeNPs improved these attributes in both control and drought conditions. Malondialdehyde, H2O2, relative membrane permeability (stress indicators) and the activities of antioxidants were increased in response to drought stress. Fe supplements further improved the antioxidant defense activities and efficiently lowered the effects of stress indicators. These effects of FeCl3 and FeNPs resulted in improved growth of S. oleracea plants in control and drought conditions. Results showed that FeNPs had more prominent effects on growth of S. oleracea plants compared to FeCl3. These findings suggest that FeNPs could be a helpful tool for lessening the harmful consequences of drought stress and this can be used for abiotic stress alleviation in other crops as well.